Implementasi model pembelajaran REACT untuk meningkatkan pemahaman konsep fisika - Ketut Kariasa (Indonesian Journal of Educational Development, 2020)
This study aims to improve understanding of the physics concepts of class X MIPA 3 students at SMA Negeri 1 Kerambitan in the 2017/208 academic year through the implementation of the REACT learning model. The research subjects were students of class X MIPA 3 at SMA Negeri 1 Kerambitan in the 2017/2018 school year. The object of research is understanding the concept of physics. Data were collected using a physics learning achievement test. The data analysis technique used a qualitative descriptive technique. The results show that the implementation of the REACT learning model can improve understanding of the physics concepts of class X MIPA 3 students in SMA Negeri 1 The 2017/2018 school year updates. This can be seen from the average value of students' understanding of physics concepts in the first cycle of 70.4 with 74% classical completeness and 74.85 in the second cycle with good categories and 94% classical completeness. The implementation of the REACT model in learning causes an increase in students' understanding of physics concepts. Penelitian ini bertujuan untuk meningkatkan pemahaman konsep fisika siswa kelas X MIPA 3 SMA Negeri 1 Kerambitan Tahun Pelajaran 2017/208 melalui implementasi model pembelajaran REACT. Subjek penelitian adalah siswa kelas X MIPA 3 di SMA Negeri 1 Kerambitan tahun pelajaran 2017/2018. Objek penelitian adalah pemahaman konsep fisika. Data dikumpulkan mengginakan tes prestasi belajar fisika. Teknik analisis data menggunakan teknik deskriptif kualitatif. Hasil penelitian menunjukkan bahwa implementasi model pembelajaran REACT dapat meningkatkan pemahaman konsep fisika siswa kelas X MIPA 3 di SMA Negeri 1 Kerambitan tahun pelajaran 2017/2018. Hal ini dapat dilihat dari nilai rata-rata pemahaman konsep fisika siswa pada siklus I sebesar 70,4 dengan ketuntasan klasikalnya 74% dan siklus II menjadi 74,85 dengan kategori baik dan ketuntasan klasikalnya 94%. Implementasi model REACT dalam pembelajran menyebabkan terjadinya peningkatan pemahaman konsep fisika siswa.